Economic assessment of the Igbo entrepreneurship model for entrepreneurial development in Nigeria: Evidence from clusters in Anambra State - Chukwunonso Ekesiobi; Stephen Kelechi Dimnwobi (African Governance and Development Institute (AGDI), 2020)
Purpose - This study presents an economic investigation of the entrepreneurship practise of the Igbos of South-Eastern Nigeria. It is intended to deepen entrepreneurial development and employment generation in the country. This study also provides empirical support to situate the Igbo entrepreneurship model (IEM) among existing entrepreneurship literature, particularly for research in developing countries. Design/methodology/approach - The study adopts a quantitative approach to examine 1187 responses carefully drawn from the Onitsha and Nnewi business clusters in Anambra state. In addition to descriptive demonstrations, the Propensity Score Matching (PSM) technique is employed to estimate the effects of treatment on the treated by pairing treatment and control units with similar attributes on the propensity score and other likely covariates. Specifically, the PSM is used to perform a counterfactual analysis of the effect of the entrepreneurship model on business outcomes by examining participants and non-participants in the IEM. Findings - The key findings of the study indicate that entrepreneurs who participated in the IEM have higher business survival rate, business growth rate and access to trade and informal credit, while non-IEM entrepreneurs have better access to formal credit source than the IEM graduates. Research Limitations/Implications - Generalisation of results can be limited since the study is based on responses of samples drawn from two clusters (Onitsha and Nnewi) in Anambra State, South-East Nigeria. The clusters, though situated in Igbo land, are not the only Igbo business locations in the South-East region and the rest of the country. However, with the larger number of the respondents and synchronisation with existing literature in this subject area guarantee the robustness and applicability of the study findings. Originality/value - The novelty of this study rests on its pioneering attempt to empirically examine how the IEM can drive entrepreneurial development in Nigeria. We also distil lessons for evidenced-based replication of the model to provide a sustainable employment channel for the country. The study posits, among other things, that the IEM can be a veritable approach for enterprise development and youth employment in Nigeria.
Keywords: 330; Igbo Entrepreneurship Model; Business outcomes; Clusters; NigeriaPaper Type: Research Paper